Literatur Review Pengaruh Kecemasan Ibu Hamil di Masa Pandemi Terhadap Kesehatan Reproduksi - Mayasanti, Raghdah Anindya; Salim, Lutfi Agus (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
The problem related to reproductive health is received less attention for pregnant women during the pandemic. This type of population experiences more stress due to Covid-19 and is more focused to prevent the exposure of Covid-19 during their pregnancy. The existence of this article was to analyze the effect of anxiety among pregnant women during the pandemic on their reproductive health. The literature review method was used for some articles under the theme of reproductive health and the anxiety of pregnant women during the pandemic. In total, about 6 out of 28 articles met the inclusion criteria: published between 2013 to 2023, using both Bahasa Indonesia and English language, with pregnant women as subjects of the study. The result showed that during the Covid-19 pandemic, pregnant women experienced more stress and anxiety symptoms, which caused less awareness of reproductive health. Hence, it is necessary to take preventive action and education in maintaining reproductive health in pregnant women.